'Fat girls' and 'big guys': gendered meanings of weight loss surgery. Issue 5 (11th February 2015) - Temple Newhook, Julia; Gregory, Deborah; Twells, Laurie
Abstract Over 80% of weight loss surgery (WLS) patients are women, yet gender is overwhelmingly absent in WLS research. This article discusses the findings of 54 interviews with twenty‐one women and six men waiting for WLS in Newfoundland and Labrador, Canada. We critically examine the ways that gender shapes the meaning of WLS in these narratives. We explore gendered meanings in participants' perspectives on their embodied experiences before surgery, social support as they decided to undergo the procedure, and their expectations for their lives after WLS. We draw on feminist theory to explain how these findings counter the dominant gender‐neutral medical model of obesity.